2022
DOI: 10.1186/s12905-022-01699-w
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level predictors of sexual autonomy among married women in Nigeria

Abstract: Background Extant studies have established diverse individual-level and relational-level predictors of sexual autonomy among women in different countries. However, information remains scanty about the predictors beyond the individual and relational levels particularly at the community level. This study examined the multi-level predictors of sexual autonomy in Nigeria. This was done to shed more light on the progression toward attaining women-controlled safe sex in Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(102 reference statements)
1
3
0
Order By: Relevance
“…This could be due to their previous attachments with health facilities, which could expose them to reproductive health services information, including the need to take part in CC screening services. This is consistent with studies conducted in China [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could be due to their previous attachments with health facilities, which could expose them to reproductive health services information, including the need to take part in CC screening services. This is consistent with studies conducted in China [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is also supported by another study that found more autonomous women are more likely to visit a health facility for health care service than their counterparts [ 33 ]. Interventions such as increasing women’s education [ 34 , 35 ] and raising awareness about women’s sexual right [ 36 , 37 ] have been effective to improve women sexual autonomy elsewhere in the world which might be benefit to be implemented in Ethiopia. Thus, the existing national policies should consider these interventions as a means to improve women sexual autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…A study in India supports these explanations, and other previous studies, 24 , 25 that women's use of the Internet could provide them with the information needed to claim and exercise their reproductive health and rights. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Sexual autonomy is linked with women’s empowerment and has been conceptualized as a human rights issue. This is because sexual autonomy helps protect and maintain an informed decision over one’s body, one’s sexuality, and one’s sexual experience [ 12 14 ]. Evidence abounds that for a society to provide and promote women’s sexual autonomy, partner involvement cannot be overlooked as partner involvement increases awareness and recognition of women’s sexual autonomy [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%